Effect of Creep on The Long-Term Deflection of Box Girder Balanced Cantilever Bridge Structure Using B3 Model and CEB 2010 - Luki Hariando Purba; Bambang Supriyadi; Bambang Suhendro (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2023)
Creep significantly affects the long-term deflection of the prestressed concrete bridge structure. Some models often used in predicting creep do not consider the water-cement ratio. The water-cement ratio is a factor in the magnitude of creep. If the water-cement ratio is excessive, the creep will also be significant. B3 Model uses the water-cement ratio in predicting creep in prestressed concrete bridge structures and has provided good accuracy with measured deflection data. This study compares B3 Model with Model CEB 2010 to predict the effect of creep on the long-term deflection. The author modeled the bridge structure using Midas Civil 2022 v1.2 software by utilizing the construction stages analysis facility to idealize the balanced cantilever and the effect of creep on the long-term deflection. Envelope displacement of bridge B3 Model is more significant than CEB 2010. The prediction deflection of the B3 Model in 100 years of service life of the bridge is -16.34 cm, while CEB 2010 is -11.90 cm. Creep affects total deflection by 84% to 88%. Creep affects the deflection significant because, in the construction process, each box girder segment is stressed and loaded at the age of 3 days. At the age of 3 days, the elastic modulus of the concrete is still not entirely, and the cement paste on the concrete is still in the hydration process. The results showed a significant difference between B3 Model and CEB 2010. B3 Model predicts that the long-term deflection of the bridge until the end of the bridge's service life is 44% to 49% greater than the CEB 2010 model. Prediction of total deflection until the end of 100 years of bridge service life does not exceed the limit determined by SNI and CEB codes.